Analysis of complete mitochondrial genome sequence of bar-tailed Treecreeper certhia himalayana (psittaciformes: Certhiidae) - Li Xie; Ming Li; Yubao Duan (Mitochondrial DNA. Part B. Resources, 2021)
Bar-tailed Treecreeper Certhia himalayana usually lives in coniferous or mixed broadleaf-conifer forests, often crawling along the trunk. In this study, we first sequenced and described the complete mitochondrial genome and phylogeny of C. himalayana. The whole genome of C. himalayana was 16,852 bp in length, and contained 13 protein-coding genes, 22 transfer RNA genes, 2 ribosome RNA genes, and 1 non-coding control regions. The overall base composition of the mitochondrial DNA was 25.1% for A, 29.2% for T, 14.5% for C, 31.2% for G, with a GC content of 45.7%. A phylogenetic tree strongly supported that C. himalayana closely related with Family Troglodytidae by highly probability.